Character Education Values in Animation Movie of Nussa and Rarra - Riskiana Widi Astuti; Herman J Waluyo; Muhammad Rohmadi (Budapest International Research and Critics University, 2019)
Character education value is needed in the education world. This study discussed a study of character education values through animation movie object of nussa and rarra, i.e. (1) religious character education value, (2) curiosity character education value, (3) friendly/communicative character education value, (4) social care character education value, (5) responsibility character education value. The researcher only limited five values of character education and used an animation movie object of nussa and rarra because the movie was trending in Indonesia. This study used survey methods and content analysis with qualitative research type because the data generated in the form of descriptions of speech fragments in the animation movie of nussa and rarra, then it divided into five types of utterances that contained the character education values and last, it analyzed. The result revealed that speech in an animation movie of nussa and rara, only five types of character education were found